About New Forms of Colonization in Occupational Therapy. Reflections on the Idea of Occupational Justice from a Critical-Political Philosophy Perspective [Sobre as Novas Formas de Colonização Em Terapia Ocupacional. Reflexões Sobre Justiça Ocupacional Na Perspectiva de Uma Filosofia Política Crítica] [a Propósito de Nuevas Formas de Colonización en Terapia Ocupacional. Reflexiones Sobre la Idea de Justicia Ocupacional Desde la Perspectiva de Una Filosofía Política Crítica] - Guajardo-Cordoba, A (Universidade Federal de Sao Carlos, 2021)
Based on a critical political philosophy position, this is a reflection of the emergence of a variety of new concepts in North-Eurocentric occupational therapy. In this new prolific and technocratic grammar, the idea of Occupational Justice (OJ) has largely resulted in this scenario, as well as in other spaces on the periphery of the global world system of the profession, particularly in academia. I maintain that the idea of Occupational Justice (OJ) has become a new form of epistemic and cognitive colonization of the profession, which operates under universalist, essentialist, liberal assumptions, typical of modern Eurocentric rationality. This idea of a single, homogeneous justice, associated with the notion of occupation would allow occupational therapy (OT) to methodologically fulfill its professional and disciplinary work structured under scientific assumptions and respond appropriately to the new complexities of its work. In the development of the text, the idea of justice is recognized as a notion that derives from political philosophy. The definition of justice and fairness is presented, according to political philosophy in its liberal and communitarian aspects. The scope of the idea of OJ and its colonial implications are delimited, an idea of Justice is proposed based on a critical ethical-political criterion, not an instrumental technical one, based on the idea of good living, under a pluricultural logic, of an anti-capitalist, communitarian order and that it materializes an expression of situated human rights, based on the recognition of difference. © This is an Open Access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.